ANALISA KINERJA PENYELENGGARAAN SENSUS PAJAK NASIONAL DI PULAU JAWA - PUSPITASARI, MINARTI (Jurnal Akuntansi AKUNESA, 2012)
Indonesia as State of amends, about problem about state development finances always need big fund. To it state acceptance source the greatest namely sectorallies taxes one can maybe at optimizes to fund that thing. This study utilizes one kualitatif's approaching with one descriptive analysis that works through a topic by give delineation about that topic. Taxes census at Java already walks good at year 2011 result new assessable data updates and give accepting ascension contributions taxeses average as big as 18%, expected by taxes census development year 2012 can more maximal with collaboration of government, society socialization and more media role extended.keywords: taxes census, socialization, taxes acceptance